(untitled) (ModaPalavra e-periódico, 2016)
The issues that permeate sustainability are increasingly present in daily life, no different in the fashion industry. Within these interrogative, it is the issue of solid waste, which challenges business, government and society todevelop strategies for their reduction and elimination. Thus, in view of the growing concern and representatively that the textile and apparel sector has, at national and international level, this article comes to add as bibliographic references, and by presenting real case, seeking clarity on, focused on strategy distinctive design, aimed at reduction and elimination of textile waste in rectilinear knitting.